On the importance of time in carbon sequestration in soils and climate change mitigation - Muñoz, Estefanía (2024)
A clear definition of carbon (C) sequestration in soils is necessary to accurately quantify the role of soil in climate change mitigation. Don et al. (2023) proposed defining carbon sequestration as “[the] Process of transferring carbon from the atmosphere into the soil through plants or other organisms, which is retained as soil organic carbon (SOC) resulting in a global C stock increase of the soil”. This definition is based on the definitions provided by IPCC (2001) and Olson et al. (2014). We agree with Don et al. (2023) that this term is often used misleadingly, which may lead to erroneous or biased quantifications of the role of soil in climate change mitigation. However, in our view, the definition proposed by Don et al. (2023) is incomplete and misses important previous discussions on the topics of permanence and the time carbon spends stored in soil. A comprehensive definition of carbon sequestration should explicitly include the time that carbon remains stored in an ecosystem and remains removed from the atmosphere, thus mitigating its contribution to the greenhouse effect.